Coupled high and low-frequency ultrasound remediation of PFAS-contaminated soils - Jitendra A. Kewalramani; Boran Wang; Richard W. Marsh; Jay N. Meegoda; Lucia Rodriguez Freire (Ultrasonics Sonochemistry, 2022)
Solids such as soils and sediments contaminated with per- and polyfluorinated alkyl substances (PFAS) from exposure to impacted media, e.g., landfill leachate or biosolids, direct contaminated discharge, and contaminant transport from atmospheric deposition, have caused significant environmental pollution. Such solids can act as secondary sources of PFAS for groundwater and surface water contamination. There are currently no proven technologies that can degrade PFAS in soil and sediments in a cost-effective, environmentally-friendly, and energy-efficient manner. This study examines the use of coupled high and low-frequency ultrasound in desorbing and degrading PFAS in soil, thereby achieving concurrent treatment and destruction of PFAS in soil. Two common PFAS, namely perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS), were used to evaluate treatment performance in soils with both low and high organic matter contents. The test results showed that the ultrasound treatment could significantly reduce PFAS concentrations in artificially contaminated soil; however, no significant degradation was achieved. Ultrasound treatment did improve desorption of PFAS from solid particles, particularly from the highly absorbent organic soil; 68.8 ± 1.8% of PFOA and 45.4 ± 4.1% of PFOS were leached from the soil after ultrasound treatment compared to only 28 ± 0.2% of PFOA and 1 ± 3.1% of PFOS after desorption in water. This work shows that sonication treatment is an effective technology for the removal of PFAS from solids, however, the presence of solids in the solid–liquid slurry can negatively impact ultrasonic cavitation, inhibiting the sonolytic degradation of desorbed PFAS.